2021
DOI: 10.3390/biology10121311
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Myosepta Development and Transcriptome Profiling between Blunt Snout Bream with and Tilapia without Intermuscular Bones

Abstract: Intermuscular bones (IBs) are small spicule-like bones located in the myosepta of basal teleosts, which negatively affect the edibleness and economic value of fish. Blunt snout bream (Megalobrama amblycephala, with epineural and epipleural IBs) and tilapia (Oreochromis niloticus, without epineural and epipleural IBs) are two major aquaculture species and ideal models for studying the formation mechanisms of fish IBs. Here, we compared myosepta development between M. amblycephala and O. niloticus, based on hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…After the findings of natural specimens of tambaqui lacking intermuscular bones [27], research has revealed the genes associated with the absence of intermuscular bones [30]; as such, the genetic and molecular mechanisms underlying the expression of such desirable phenotypes are currently better known [34]. Current genome-editing techniques, such as CRISPR-Cas9 [35], can be developed to generate new IB-defected strains; however, methods such as X-ray imaging can be essential, complementary and integrative in deducing and describing the IB morphology [18,20,36]. Between these two methods, X-ray imaging to count and measure IBs is a rapid and non-invasive technique and has thus recently become a very convenient and popular approach for various fish species [26,27,37].…”
Section: Discussionmentioning
confidence: 99%
“…After the findings of natural specimens of tambaqui lacking intermuscular bones [27], research has revealed the genes associated with the absence of intermuscular bones [30]; as such, the genetic and molecular mechanisms underlying the expression of such desirable phenotypes are currently better known [34]. Current genome-editing techniques, such as CRISPR-Cas9 [35], can be developed to generate new IB-defected strains; however, methods such as X-ray imaging can be essential, complementary and integrative in deducing and describing the IB morphology [18,20,36]. Between these two methods, X-ray imaging to count and measure IBs is a rapid and non-invasive technique and has thus recently become a very convenient and popular approach for various fish species [26,27,37].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β isoforms have other effects during wound healing and scarring. While TGF-β3 is a significant inducer of Scx, which is expressed early in tendon development initiating tendon differentiation, it is also an inhibitor of collagen fiber maturation during tenogenic differentiation, especially in the late stage ( Perucca Orfei et al, 2019 ; Zhou et al, 2021a ). TGF-β3 alone or combined with other GFs acts as an essential tenogenic inducer in many cell types, such as AD-MSCs ( Shojaee et al, 2022 ), human tenocytes ( Tsiapalis et al, 2021 ), BMSCs ( Bottagisio et al, 2017 ), embryo-derived stem cells (ESCs) ( Barsby et al, 2014 ), tonsil-derived MSCs (TMSCs) ( Wee et al, 2022 ).…”
Section: Gfs In At Injurymentioning
confidence: 99%
“…Comparing species with and without epineural and epipleural IBs or fish strains with different abundances of them could provide interesting clues for reducing the number of IBs. Zhou et al [ 26 ] analyzed different stages of myosepta development using morphological and transcriptomics analyses in blunt snout bream ( Megalobrama amblycephala ) and Nile tilapia ( Oreochromis niloticus ), fish species with and without epineural and epipleural IBs, respectively. Among other results, the authors identified a repertoire of genes that may play important roles in IB development, with could provide interesting information for further studies [ 26 ].…”
mentioning
confidence: 99%
“…Zhou et al [ 26 ] analyzed different stages of myosepta development using morphological and transcriptomics analyses in blunt snout bream ( Megalobrama amblycephala ) and Nile tilapia ( Oreochromis niloticus ), fish species with and without epineural and epipleural IBs, respectively. Among other results, the authors identified a repertoire of genes that may play important roles in IB development, with could provide interesting information for further studies [ 26 ]. On the other hand, Cui et al [ 27 ] conducted whole-genome resequencing and bulked segregant analysis in three common carp strains with a different abundance of IBs to identify SNPs that could be associated with the number of IBs.…”
mentioning
confidence: 99%